Doing ethnography today theories, methods, exercises - Campbell, Elizabeth; Lassiter, Luke E. (Chichester, West Sussex, [England] Wiley-Blackwell, 2015)
"Provides guidance on interview questions and selecting appropriate field equipment"--Provided by publisher.
1. Introduction: Conceptualizing ethnography -- 2. Fields of collaboration -- 3. Emergent design -- 4. Engagement: participation and observation and observant participation -- 5. Interviews and conversations -- 6. Inscriptions: on writing ethnography Exercise.
Includes bibliographical references and index.
Keywords: Ethnology -- Handbooks, manuals, etc; Ethnology -- Study and teaching